Placental morphology in pre-eclampsia and eclampsia and the likely role of NK cells - Maham Akhlaq; Abdul H Nagi; Ahmad Waseem Yousaf (Wolters Kluwer Medknow Publications, 2012)
Background: Placenta has long been a neglected organ as far as its pathology is concerned. This study is an attempt to observe the morphological features of placentae both gross and microscopic in normal pregnancy, preeclampsia, and eclampsia. Materials and Methods: A total of 150 placentae were collected; of these, 50 belonged to normal pregnancy, 50 belonged to pre-eclamptic women, and 50 were from patients of eclampsia. Results: Placental trimmed weight was seen to be decreased in patients of preeclampsia and eclampsia. Placental infarcts were more commonly seen in the diseased group and they were more centrally located. Hypertrophy of the spiral arterioles was observed in the decidual portion found in placental disc and membranes. Distal villous hypoplasia was also frequently seen in the diseased group. Fetal membranes were thickened and showed infarcts in preeclampsia and eclampsia. Conclusions: Morphological features seen in eclamptic placentae were similar but exaggerated compared to preeclampsia. In conclusion, the pathological changes were found to be more severe and frequent in preeclampsia and eclampsia, but more so in eclamptic placentae as compared with placenta of normal pregnancy. CD56 immunomarker was also used to identify NK cells. They were found to be present only in the diseased group and were located in the decidual portion of the basal plate, implicating their role in the development of the disease.